Application Of Composite Performance Index (Cpi) Method In Decision Support System Election Of Best Village Head In North Bengkulu District - Andre pranata, Andre Pranat; Supardi, Reno; Fredricka, Jhoanne (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2024)
The selection of the best village head is one of the programs of North Bengkulu Regency with the aim of improving the performance of each elected village head. A decision support system is an alternative system that aims to help make decisions through the use of data and decision models to solve semi-structured and unstructured problems. The aim of this research is to build a decision support system by applying the composite performance index (CPI) method as a decision making method that is able to assist the district in assessing the best village head according to predetermined criteria. This research produces a system that can help provide recommendations for the best village heads based on calculations of criteria set by the selectors.